LITERATURE STUDY: IMPROVING LINGUISTIC INTELLIGENCE AND CHARACTER OF ELEMENTARY SCHOOL STUDENTS THROUGH CHILDREN’S FAIRY TALES - Dini Dawamah; Robi'atul Adawiyah; Vady Nisa Anugrah; Yulia Hidayatul Rohmah; Conny Dian Sumadi (Citra Dharma Cindekia, 2022)
The storytelling method is a way to achieve learning objectives so that students are more enthusiastic in participating in a lesson because storytelling is an interesting and fun method for elementary school children who are learning to speak and communicate with their interlocutors. In improving children's linguistic/language intelligence, appropriate learning methods are needed so that students can hone and have qualified linguistic intelligence, for example by using the storytelling method. The purpose of this study was to determine whether storytelling can improve linguistic intelligence and teach character education to elementary school children. This research uses a qualitative research type. Qualitative research is a type of descriptive research that usually uses analysis. This research also uses literature study or literature study. The results of the study stated that using the storytelling method, especially children's fairy tales, was able to improve character education and linguistic intelligence of students in elementary schools.